Effect of the application of humanized nursing care on the clinical outcomes of neonates with hyperbilirubinemia - Sahar Mahmoud Elkhedr Abdelgawad; Eman Salah Elmetwaly Abdelrahman Galalah; Heba Saied El-mahdy; Nagafa Hafez Farag Elmahdy (BMC Nursing)
Abstract Background Neonatal hyperbilirubinemia is a potentially fatal condition that has toxic effects on the brain and may have negative effects. Humanized care is a comprehensive approach that focuses on the nutritional, therapeutic and hygienic needs of neonates, which helps in the resolution of hyperbilirubinemia. Method A quasi-experimental design was utilized in this study to evaluate the effect of humanized nursing care application on the clinical outcomes of neonates with hyperbilirubinemia. It was carried out at the Neonatal Intensive Care Unit at Tanta Main University Hospital. A total of 120 neonates with hyperbilirubinemia who fit the inclusion criteria were randomly assigned to both the study and control groups. The data were collected using the biosocial-demographic characteristics of the studied neonates and neonatal clinical outcome measures for humanized care. Results On the seventh day after receiving humanized care, total bilirubin levels in the study group decreased to 4.03 ± 1.48 compared to 10.21 ± 2.08 in the control group; there was also a decline in the time of jaundice regression with a mean of 3.966 ± 1.09 in the study group compared to 4.66 ± 1.29. in the control group. The mean days of phototherapy were 1.83 ± 0.73 in the study group and 2.41 ± 1.01 in the control group. Additionally, oxygen saturation increased significantly on the 7th day in the study group compared to the control group; the mean amount of daily milk intake was 752.8 ± 262.9 ml in the study group compared with 600.76 ± 290.31 ml in the control group. Conclusion Applying humanized care improved neonatal clinical outcomes, including O2 saturation, jaundice regression, enhanced newborn feeding and decreased duration of phototherapy.